2020
DOI: 10.1182/blood.2020005278
|View full text |Cite|
|
Sign up to set email alerts
|

Optimized tandem CD19/CD20 CAR-engineered T cells in refractory/relapsed B cell lymphoma

Abstract: Chimeric antigen receptor T (CAR T) cells targeting CD19 have achieved breakthroughs in the treatment of hematological malignancies, such as relapsed/refractory non-Hodgkin lymphoma (r/rNHL); however, high rates of treatment failure and recurrence after CAR T cell therapy are considerable obstacles to overcome. In this study, we designed a series of tandem CARs (TanCARs) and found that TanCAR7 T cells not only showed dual antigen targeting of both CD19 and CD20 but also formed superior and stable immunological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
181
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(186 citation statements)
references
References 44 publications
3
181
0
2
Order By: Relevance
“…In addition, poor T-cell persistence is also a relatively common situation and contributes to a proportion of relapses. It is worth noting that membrane binding location, linker length between the heavy and light chains and other spatial considerations are all important for the efficacy and safety of CAR T-cells, which is more complex in the incorporation of multiple scFvs ( 51 , 173 , 174 ). More basic studies are required to optimize the structure of multitargeting CARs in pursuit of better clinical outcomes.…”
Section: Clinical Strategiesmentioning
confidence: 99%
“…In addition, poor T-cell persistence is also a relatively common situation and contributes to a proportion of relapses. It is worth noting that membrane binding location, linker length between the heavy and light chains and other spatial considerations are all important for the efficacy and safety of CAR T-cells, which is more complex in the incorporation of multiple scFvs ( 51 , 173 , 174 ). More basic studies are required to optimize the structure of multitargeting CARs in pursuit of better clinical outcomes.…”
Section: Clinical Strategiesmentioning
confidence: 99%
“…Expressing dualtargeted CAR molecules (tandem CARs) is another combination strategy. In 2020, Tong et al 41 found that optimized tandem CAR T-19/20 cells could form a more stable immunological synapse, leading to better antitumor function. The dual-targeted CAR T cells were then tested in R/R NHL patients, and a total of 28 patients received CAR T-19/20 treatment.…”
Section: Hematological Malignancies Cd19mentioning
confidence: 99%
“…Grade 3 CRS occurred in 14% of patients and 17% required tocilizumab for management. There were no three quarter grade neurological toxicities [ 36 ]. An update of this study was provided in abstract form in June 2020 which reported on outcomes of 87 patients.…”
Section: Dual Targeting In B-cell Malignanciesmentioning
confidence: 99%